Management of intruded primary teeth using computer-controlled local anesthetic delivery systems: Tatalaksana gigi susu yang intrusi menggunakan sistem anestesi lokal yang dikendalikan komputer - Permatasari, Andi Sri; Syahrir, Syakriani; Inayah, Yayah; Wijaya, Wiwik Elnangti; Hamudeng, Adam Malik; Nurrahma, Rifaat; Alwi, Ita Purnama (Makassar Dental Journal, 2025)
Intrusion is the most common trauma in children. Management of intruded deciduous teeth includes spontaneous re-eruption or ex-traction. Pain management during extraction is performed with local anaesthesia, but this can cause fear and pain in patients. This case report describes the management of an intruded primary tooth using a computer-controlled local anaesthesia system (CCLAD). A 6-year-old boy presented with an intruded maxillary primary incisor following a fall from stairs the previous day. Clinical findings included swelling and ulceration of the lip and chin, haematoma, and gingival ulceration. Ellis Class IX fractures were no-ted in teeth 51, 61, and 62 with severe intrusion (grade III), slight mobility, and fusion of 61-62. Panoramic imaging revealed age-nesis of teeth 22. After one week of observation for spontaneous re-eruption, extraction of teeth 51, 61, and 62 was performed due to the risk to the permanent replacement teeth. Anaesthesia was administered using the P-ASA (palatal-alveolar superior anterior) technique with SleeperOne5 (CCLAD), improving patient comfort and reducing fear. Monitoring over 12 months showed no com-plications. It was concluded that SleeperOne5 as a CCLAD with the P-ASA anaesthesia approach is a useful alternative for ma-naging multiple impacted anterior deciduous teeth.